The Era of Global Risk An Introduction to Existential Risk Studies - Beard, SJ; Richards, Catherine; Rios Rojas, Clarissa (Open Book Publishers, 2023)
This innovative and comprehensive collection of essays explores the biggest threats facing humanity in the 21st century; threats that cannot be contained or controlled and that have the potential to bring about human extinction and civilization collapse. Bringing together experts from many disciplines, it provides an accessible survey of what we know about these threats, how we can understand them better, and most importantly what can be done to manage them effectively. These essays pair insights from decades of research and activism around global risk with the latest academic findings from the emerging field of Existential Risk Studies. Voicing the work of world leading experts and tackling a variety of vital issues, they weigh up the demands of natural systems with political pressures and technological advances to build an empowering vision of how we can safeguard humanity's long-term future. The book covers both a comprehensive survey of how to study and manage global risks with in-depth discussion of core risk drivers: including environmental breakdown, novel technologies, global scale natural disasters, and nuclear threats. The Era of Global Risk offers a thorough analysis of the most serious dangers to humanity. Inspiring, accessible, and essential reading for both students of global risk and those committed to its mitigation, this book poses one critical question: how can we make sense of this era of global risk and move beyond it to an era of global safety?